10. DETEKSI BILIRUBIN URINE ORANGUTAN SUMATERA (Pongo abelii) MENGGUNAKAN STRIP TEST SEMIKUANTITATIF DI PUSAT REINTRODUKSI JANTHO Detection of Bilirubin on sumatran Orangutan (Pongo abelii) Urine Using Semiquantitative Strip Test in Center of Jantho Reintroduction - Vicky Diawan H. (Universitas Syiah Kuala, 2016)
The aim of this study was to find out the presence of bilirubin on sumateran orangutan urine as a medical record and a supporting diagnostic of orangutan in Jantho Reintroduction Centre, Aceh Besar. The urine samples were collected from ten sumateran orangutans from forest, around the cage, and in the cage. Urine was collected in the morning when orangutan woke up and left the nest or before first feed for orangutan which was in the cage. The replication test was done eight times within four weeks. The bilirubin test was directly carried out by dipping the strip test in 5-10 mL urine for 30 second. Data were analyzed using qualitative descriptive and the result was semiquantitative, through the examination of bilirubin value using 4 scale discoloration of strip test: negative (0 mg/dL), small (1 mg/dL), moderate (2 mg/dL), and large (4 mg/dL). The result showed that bilirubin was not detected on 9 out of 10 sumateran orangutan samples, only one sumateran orangutan positively detected the presence of bilirubin which categorize in small (1 mg/dL) scale. ____________________________________________________________________________________________________________________ Key words: bilirubin, sumateran orangutan, strip test, urine